Face-to-face social interactions and local informational advantage - Lee, Robin Y. (Journal of Financial Economics, 2026)
This paper examines the causal role of face-to-face (F2F) interactions in generating local informational advantages for mutual fund managers. Using COVID-19 lockdowns as an exogenous shock, I show that fund managers’ performance on local stocks declined relative to distant stocks when in-person meetings were curtailed, driven by impaired investment timing rather than changes in firm fundamentals. I investigate two distinct benefits of F2F interactions arising from interpersonal cues: trust-building, which enhances the transmission of soft information, and impression management, which facilitates the transmission of favorable information. The results cannot be fully explained by changes in internal information flows or the use of public information, and are more pronounced for stocks in less transparent information environments and in regions with stronger social traits.